Bruxism in psychiatry - Kulo?lu, Murat; Ekinci, Okan (My University, 2009)
Bruxism, which is characterized by clenching and/or grinding of the dentition, is a common condition affecting approximately 8 to 21 percent of the population. Bruxism is mainly associated with rhythmic masticator muscle activity characterized by repetitive jaw muscle contractions. The neurochemical mechanisms underlying sleep bruxism are little understood at present. However, recent pharmacologic evidence suggests that the imbalance between dopaminergic and serotoninergic system may be involved in the pathophysiology of bruxism. Psychiatric patients are routinely treated with various psychotropic drugs. It has been suggested that various substances related to the dopaminergic, serotoninergic and adrenergic systems ameliorate or exacerbate bruxism in humans and animals. Bruxism associated with drugs can be destructive, resulting in severe consequences to health that include destruction of tooth structure, irreversible harm to the temporomandibular joint, severe myofascial pain, and muscle contraction headache. However, reports concerning a possible association between bruxism and various psychotropic drugs are scarce and mostly anecdotal. Although an increasing number of studies on the etiology and management of bruxism, this clinical problem is still difficult to understand and as a subject open to discussion in our stands. In this review article, the effect of psychotropic drugs on bruxism, its etiology, comorbid psychiatric diagnosis and current treatment methods are discussed with the light of previous literature.
Psikiyatride bruksizm
Keywords: Bruxism; Dopamine; Psychotropic drugs; Serotonin